Comparison of P-POSSUM and Cr-POSSUM scores in patients undergoing colorectal cancer resection in Hospital Taiping - Zahidi, Zaidatul-Zarina Mohd (2017)
Introduction : P-POSSUM and Cr-POSSUM are two common scoring systems used in predicting post-operative mortality in surgical patients. Objectives : The objective of this study was to assess the accuracy of P-POSSUM and Cr- POSSUM systems in predicting post-operative mortality in patients with colorectal cancer in Hospital Taiping. Methods : It was retrospective cohort study of patients after resection of colorectal cancer (CRC). Patients who underwent CRC resection from April 2013 to April 2015 at Hospital Taiping will be retrospectively included in the study. Those patients for whom P-POSSUM and Cr-POSSUM scores could not be calculated because of lack of data will be excluded. Physiologic scores and operative severity scores for both P-POSSUM and Cr-POSSUM will be calculated for each patients based on their medical records. In- Hospital mortality and death within 30 days after colorectal surgery were recorded. Data will be analyze using the linear method of analysis described by Wijesinghe et al; where, in this type of analysis, patients are stratified into groups based on the predicted risk of death. Expected number of deaths is then calculated for each risk group by multiplying the number of patients in a given group with average risk of death in that group. The ratio of observed to expected deaths (O/E ratio) will be calculated for each analysis. The X² test of Lemeshaw and Hosmer will be used to assess any differences between predicted and observed morbidity and mortality rates. Discrimination ability,that is, the ability of the model to assign higher probabilities of death to those patients who died, was measured using receiver operating characteristic curves, which were analyzed for both scores. P<0.05 will be considered statistically significant. Results : Eighty seven patients included in study. The number of deaths predicted by Cr- POSSUM with linear analysis when all patients were analyzed. The Observed / Expected (O/E) ratio for all risk group was 1.5, indicating that the Cr-POSSUM system under predicted mortality in this study by 50%. However, there was no significant difference between the observed and predicted values (X² = 2.33; P= 0.51). On the other hand, P-POSSUM system seemed predicting mortality well in this study, with an overall O:E ratio of 1. There were no significant difference between the predicted and observed values (X²=1.5; P=0.91). Discriminatory power of P-POSSUM and Cr- POSSUM scores in predicting death as an outcome measure was analyzed using receiver operating characteristic (ROC) curves. Area under the receiver operating characteristic curve (AUC) for Cr-POSSUM was 0.831 (95% confidence interval (CI) , 0.681-0.981). For P-POSSUM, the AUC was 0.857 (95% CI, 0.762-0.951), indicating satisfactory discriminatory power. Conclusions : In conclusion, the results of present study demonstrate that both P-POSSUM and Cr-POSSUM are a useful scoring system that performs well in prediction of mortality after surgery in colorectal patients. Both scoring system performed equally good and specialized scoring systems (Cr-POSSUM) show no superiority over P-POSSUM in predicting mortality after surgery.